1978
DOI: 10.1007/bf00261317
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone metabolism in patients with advanced carcinoma of the prostate: A comparative in vivo study of the effect of oestrogen and anti-prolactin

Abstract: In the light of the high incidence of cardiovascular side effects with oestrogen therapy in patients with prostatic cancer, other medications altering androgen metabolism are under investigation. The influence of the anti-prolactin bromocriptin (CB157) on plasma kinetics of testosterone and on endogenous hormones was studied and compared with the effect of ethinyl oestradiol in 25 patients with prostatic carcinoma. Bromocriptine significantly suppressed both prolactin and testosterone, inhibited the transfer o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1982
1982
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Interestingly, activation of prolactin receptor signaling has been associated with prostate tumorigenesis and cancer progression, leading to the hypothesis that the blockade of pituitary prolactin production by bromocriptine could benefit PCa patients (47). Indeed, several pilot trials have been performed in castration-resistant PCa (4850), which showed that bromocriptine administration (for example, 2.5 mg, three times per day) was well tolerated and significantly reduced the plasma levels of prolactin and testosterone. However, the bromocriptine-associated responses varied among these studies from an overall objective regression of 22.2% (and 50% of the patients had a prompt relief of bone pain) to no complete or partial responses in evaluable patients.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, activation of prolactin receptor signaling has been associated with prostate tumorigenesis and cancer progression, leading to the hypothesis that the blockade of pituitary prolactin production by bromocriptine could benefit PCa patients (47). Indeed, several pilot trials have been performed in castration-resistant PCa (4850), which showed that bromocriptine administration (for example, 2.5 mg, three times per day) was well tolerated and significantly reduced the plasma levels of prolactin and testosterone. However, the bromocriptine-associated responses varied among these studies from an overall objective regression of 22.2% (and 50% of the patients had a prompt relief of bone pain) to no complete or partial responses in evaluable patients.…”
Section: Discussionmentioning
confidence: 99%
“…The general finding is that low-to-moderate levels of Prl potentiate the trophic effects of testosterone on prostatic growth but that, beyond optimal levels, the lactogen becomes an inhibitor of both normal and neoplastic growth. These relationships have clinical significance since there is an inverse relationship between survival and serum prolactin levels in prostatic cancer patients [ 1,2], and stabilization or remission of the disease has been found to follow prolactin depletion [3,4].…”
Section: Introductionmentioning
confidence: 95%
“…Suppression of prolactin release by bromocriptine reduced the weight of androgen-dependent organs in animal studies . In addition, antiprolactins show an analgesiceffectin many patients with bone pain from skeletal metastasis (Jacobi et al 1978). The therapeutic use of prolactin-inhibiting substances in these patients is well established.…”
Section: Effects On Accessory Glandsmentioning
confidence: 99%